2021
DOI: 10.1152/jn.00588.2020
|View full text |Cite
|
Sign up to set email alerts
|

Music-selective neural populations arise without musical training

Abstract: Recent work has shown that human auditory cortex contains neural populations anterior and posterior to primary auditory cortex that respond selectively to music. However, it is unknown how this selectivity for music arises. To test whether musical training is necessary, we measured fMRI responses to 192 natural sounds in 10 people with almost no musical training. When voxel responses were decomposed into underlying components, this group exhibited a music-selective component that was very similar in response p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(106 citation statements)
references
References 120 publications
6
99
1
Order By: Relevance
“…However, dramatic changes of such preexisting functional elements are unlikely, according to recent experimental studies. It was reported that music-selectivity is similarly observed in both musicians and non-musicians who had almost no explicit training in music (11). Furthermore, native Amazonians who had almost no exposure to Western harmony showed similar characteristics of perceiving musical harmonics as Westerners (15), while aesthetic judgments of musical intervals (consonance/dissonance in Western music) can be largely dependent on culture (52).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, dramatic changes of such preexisting functional elements are unlikely, according to recent experimental studies. It was reported that music-selectivity is similarly observed in both musicians and non-musicians who had almost no explicit training in music (11). Furthermore, native Amazonians who had almost no exposure to Western harmony showed similar characteristics of perceiving musical harmonics as Westerners (15), while aesthetic judgments of musical intervals (consonance/dissonance in Western music) can be largely dependent on culture (52).…”
Section: Discussionmentioning
confidence: 99%
“…1A, 17,902 training data and 17,585 test data with balanced numbers for each category to avoid overfitting for a specific class). Each excerpt in the dataset is intrinsically multi-labeled as different sounds generally co-occur in a natural environment, but a sufficient number of data was selected to contain only music-related categories (3,620 in the training set and 4,033 in the test set) and no music-related categories (11,087 in the training set and 10,616 in the test set). These sets can be safely termed as 'music' and 'non-music' sounds, respectively.…”
Section: Distinct Representation Of Music In a Network Trained For Natural Sound Detection Including Musicmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of the VWFA implies that finding brain regions which respond selectively to music vs. other sounds (i.e., regions "neurally selective for music") would not help resolve the Darwin-James debate. Indeed, there is now robust evidence for such regions, which is interesting because to date the only sounds for which category-selective neural regions have been found are speech and music (Norman-Haignere et al 2015;Boebinger et al 2021). Yet music-selective brain regions, like the VWFA, could result from experience-dependent neural plasticity since music is a complex, meaningful sound pattern heard throughout life.…”
Section: Introductionmentioning
confidence: 98%
“…The bilateral superior temporal regions show music-selective neural responses ( Fedorenko et al. 2012 ; Boebinger et al. 2021 ).…”
Section: Introductionmentioning
confidence: 99%